Pengaruh Pengungkapan Informasi Aktivitas Sosial Perusahaan Terhadap Kinerja Keuangan Perusahaan - Fanani, Baihaqi; Jalil, Mahben (PERMANA, 2013)
The objective of this research is to examine what social activities disclosures switch with consumers andproducts, environment and energy, business partners, stockholders, communities and labors in annualfinancial report have the positive effect to development stock price. The object of this research are foodand beverage companies listed in Indonesian Stock Exchange in 2011. To know and measur therelationship between enterprise social activities disclosures with development stock price usedmultivariate regression analysis. The analysis result R value is 0.212, adjusted RÂ²-0.313, F test value0.404 with significant degree 0.859 and t test value for every variable 1.208, -0.805, 0.608, -0.428, 0.078and 0.070 with significant degree 0.258, 0.442, 0.558, 0.679, 0.940 and 0.946. Social activitiesdisclosures switch with consumers and products, environment and energy, business partners,stockholders, communities, and labors have no significant doubt to development price stock because thesignificant degree higher than 0.05.Keywords: Social Activities Disclosures, Business Partners, Consumers and Products, Societies, Laborsand Stockholders.